Increased carbohydrate oxidation after ingesting carbohydrate with added protein - Betts, J. A.; Williams, C.; Boobis, L.; Tsintzas, K. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To examine the metabolic impact of including protein in a postexercise carbohydrate supplement when ingested between two bouts of prolonged running performed within the same day.